Caracterização parcial e imobilização covalente da Neutrase® comercial - Manzolli, Bruna Luiza de Jesus (Universidade Federal de São Carlos, 2023)
The use of enzymes as agents for modifying the functional properties of proteins has been widespread, mainly in the food industry. One of the most studied groups for this purpose are the proteases. Proteases are responsible for breaking peptide bonds between amino acids in proteins, producing smaller peptides and functional free amino acids. The use of the Neutrase® enzyme is explained by the fact that it is a protease that hydrolyses whey proteins, a highly polluting by-product and, most of the time, discarded in the dairy industries, aiming at obtaining derivatives with better functional properties. The general objective of this work was to partially characterize the crude extract of commercial Neutrase® derived from a Bacillus sp. The results obtained showed in the first enzymatic assay of free neutrase, its activity, determined through spectrophotometric analysis, was 27.9 U/mL. The total protein dosage found in the assay resulted in a value of 0.94 mg/mL. At the optimal activity temperature, 55 °C, the protease remained stable for a few hours. In addition, with the use of metallic ions, a characteristic of the existence of metalloproteases in the extract was observed. Regarding covalent immobilization, two supports were tested and the activity values of the Neutrase-Glyoxyl-Cob Corn (NGSM) and Neutrase Glyoxyl-Agarose (NGA) derivatives were 1.04 U/g and 1.15U/g, respectively. In addition to immobilization yields below expectations, unsatisfactory values for the methodology used. Despite this, future studies with other types of immobilization and functionalization of the support may favor the hydrolytic activity of the enzyme, a fact that still makes it a possible potential for new industrial applications.
Partial characterization and covalent immobilization of commercial Neutrase®
Keywords: Protease; Neutrase; Imobilização covalente; Hidrólise; Enzima; Enzyme; Hydrolysis; Covalent immobilization; CIENCIAS BIOLOGICAS::BIOQUIMICA::ENZIMOLOGIA